Implementasi Kebijakan Perlindungan Anak Di Kota Palu - Linardy, Erick; Rivai, Abdul; Reza, Fachrul (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This research aims to explore in depth the implementation of child protection policies in Palu City and identify the factors that cause the suboptimal handling of child abuse issues. The phenomenon of increasing cases of child abuse in Palu City is a crucial background to this study. The research method used is descriptive qualitative, and this study uses George C. Edward III's policy implementation theoretical framework as the main analytical tool, which includes indicators of communication, resources, disposition, and bureaucratic structure. The unit of analysis in this study consisted of policy implementers, including the Palu City Women's Empowerment and Child Protection Agency (DP3A), UPTD PPA, PATBM, Children's Forum, and non-governmental organizations (LiBu Perempuan). Data analysis techniques were carried out through a process of data collection, data reduction, data presentation, and conclusion drawing using data collection techniques through interviews, observation, documentation, and audio-visual material. The results of the study show that policy implementation in Palu City is driven by the highly commitment of implementers, as well as a bureaucratic structure with clear service SOPs. However, implementation faces critical obstacles in terms of resources, particularly the lack of fiscal budget allocation and the limited number of specific experts (clinical psychologists). In addition, a cognitive gap was found with law enforcement officials regarding the interpretation of case resolutions. The recommendations provided include the need to synchronize budget priorities in the regional budget, establish technical human resource retention policies to prevent excessive employee turnover, and strengthen cross-sectoral coordination with vertical agencies to unify legal perceptions for maximum victim protection.